THE TURING TEST AND CONSCIOUSNESS: A PROPOSAL. - Faye, Jan (Epistemologia, 2013)
In a famous paper Alan Turing argued that in case we could not, based on the linguistic responses, decide whether a computer was a man or a machine, we should hesitate, but ascribe intelligence to it. This argument has most famously been criticized by John Searle and I think his conclusion is on the right track. However, I also believe that he cannot give an account of consciousness in terms of biological selection and adaptation because he associates consciousness with human language. In the end I come forward with a suggestion according to which qualia and consciousness can be considered as two sides of the same coin and be understood in relation to the brain's processing capacity. Qualia are what I called 'bundled information' and the consciousness is the 'reader' of this information.